Methodological challenges in a study on falls in an older population of Cape Town, South Africa - Kalula, Sebastiana Z (Afr Health Sci, 2017)
BACKGROUND: Falls are a major cause of disability, morbidity and mortality in older persons, but have been under researched in developing countries. OBJECTIVE: To describe challenges encountered in a community-based study on falls in a multi-ethnic population aged ≥65 years in a low-income setting. METHODS: The study was conducted in four stages: A pilot study (n=105) to establish a sample size for the survey. An equipment validation study (n=118) to use for fall risk determination. A cross-sectional baseline (n=837) and a 12-month follow-up survey (n=632) to establish prevalence and risk factors for falls. RESULTS: Prevalence rate of 26.4% (95% CI 23.5–29.5%) and risk factors for recurrent falls: previous falls, self-reported poor mobility and dizziness were established. Adaptations to the gold standard prospective fall research study design were employed: 1) to gain access to the study population in three selected suburbs, 2) to perform assessments in a non-standardised setting, 3) to address subjects' poverty and low literacy levels, and high attrition of subjects and field workers. CONCLUSION: Studies on falls in the older population of low- to middle-income countries have methodological challenges. Adaptive strategies used in the Cape Town study and the research experience reported may be instructive for investigators planning similar studies in such settings.